Analysis of the development Android’s runtime - Honcharenko, Kostiantyn; Smołka, Jakub (Journal of Computer Sciences Institute, 2019)
The article presents the development of the Android runtime. Own application for Android is presented, which implements performance benchmarks used to test different versions of the Android runtime. The methods measure the benchmark execution times in different versions of the Android runtime environment.